Collaboration technologies and social computing : 8th International Conference, CollabTech 2016, Kanazawa, Japan, September 14-16, 2016, Proceedings /: 8th International Conference, CollabTech 2016, Kanazawa, Japan, September 14-16, 2016, Proceedings. (2016) - Unknown
No abstract available